2018
DOI: 10.1177/0265407518788197
|View full text |Cite
|
Sign up to set email alerts
|

Positive humor in couples as interpersonal emotion regulation: A dyadic study in everyday life on the mediating role of psychological intimacy

Abstract: The aim of this study was to investigate daily positive humor in couples as an interpersonal emotion regulation strategy. Associated changes in psychological intimacy were tested as a possible socio-affective pathway of emotion regulation that mediates the effects of couple humor on changes in individual momentary affect. Within a dyadic ambulatory assessment framework, 102 couples reported on their production of positive humor as an attempt to regulate their partner’s mood, psychological intimacy, and momenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 57 publications
2
54
1
1
Order By: Relevance
“…Mother-child co-reappraisal significantly reduced the intensity of children's anger and sadness displays following a laboratory manipulation of disappointment (Morris, Silk, Morris, Steinberg, Aucoin, & Keyes, 2011). Romantic partners frequently used physical touch and positive humor in daily life in response to their partners' affective states, and the use of these interpersonal affect regulating strategies was associated with greater momentary positive affect (Debrot, Schoebi, Perrez, & Horn, 2013;Horn, Samson, Debrot, & Perrez, 2018). Finally, romantic partners were able to effectively assist their significant others' efforts to down-regulate negative affect in a laboratory emotion regulation decision-making paradigm (Levy-Gigi & Shamay-Tsoory, 2017).…”
Section: Emotional and Psychosocial Correlates Of Iermentioning
confidence: 99%
See 2 more Smart Citations
“…Mother-child co-reappraisal significantly reduced the intensity of children's anger and sadness displays following a laboratory manipulation of disappointment (Morris, Silk, Morris, Steinberg, Aucoin, & Keyes, 2011). Romantic partners frequently used physical touch and positive humor in daily life in response to their partners' affective states, and the use of these interpersonal affect regulating strategies was associated with greater momentary positive affect (Debrot, Schoebi, Perrez, & Horn, 2013;Horn, Samson, Debrot, & Perrez, 2018). Finally, romantic partners were able to effectively assist their significant others' efforts to down-regulate negative affect in a laboratory emotion regulation decision-making paradigm (Levy-Gigi & Shamay-Tsoory, 2017).…”
Section: Emotional and Psychosocial Correlates Of Iermentioning
confidence: 99%
“…In a laboratory study of social sharing and IER, people who received comfort and validation reported feeling closer to the listener after the interaction (Pauw et al, 2017). Use of physical touch and positive humor in the service of IER was associated with increased feelings of psychological intimacy in romantic relationships in a pair of ecological momentary assessment studies (Debrot, Schoebi, Perrez, & Horn, 2013;Horn, Samson, Debrot, & Perrez, 2018). Findings from multiple studies indicate that providing IER likewise has demonstrable social consequences (e.g., Niven et al, 2015;Niven, Holman, & Totterdell, 2012;Niven, Macdonald, & Holman, 2012), although we focus here on receipt of IER.…”
Section: Emotional and Psychosocial Correlates Of Iermentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, recent research on emotion regulation leaves the earlier adopted “lone man against the elements” view on regulating mood and emotion behind and underlines the role of genuinely interpersonal coregulating processes. Again, relationship quality has been shown to be a key candidate for an interpersonal pathway of emotion regulation in the literature (Debrot et al, 2013; Horn et al, 2018). Emotion regulation refers to processes that involve the activation of a goal to change, strengthen, or decrease emotional experiences and is thus a broader concept than coping as it includes the cultivation and maintenance of positive states without any demanding situations that need to be coped with (Gross, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The collection and assessment of such data is possible because smartphones are widely available and come with the computational power and sensors needed to obtain information about their owners' daily lives. Researchers in the fields of social science (e.g., Raento et al, 2009), psychology (e.g., Miller, 2012; Harari et al, 2016), and neuroscience (e.g., Schlee et al, 2016; Ladouce et al, 2017) use smartphones to collect data about personality processes and dynamics (Allemand and Mehl, 2017; Beierle et al, 2018a; Stieger et al, 2018; Zimmermann et al, 2018), daily cognitive behaviors (Aschwanden et al, 2018), social support behaviors (Scholz et al, 2016), momentary thoughts (Demiray et al, 2017), couple interactions (Horn et al, 2018), physical activity (Gruenenfelder-Steiger et al, 2017), and moods and emotions (Erbas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%